Lingvo-axiological description of ethnocultural values determination - Nagima Ilyassova, Ulan Taizhanov, (Opción)
This article discusses the concept of ‘culture’ in linguistics and the role of the ethnic group in the development of values of spiritual and material culture through language via comparative qualitative research methods. As a result, a model of the concept of ‘horse’ was developed, reflecting the theoretical aspects of ethnological assessment, ethnological study, ethnological pragmatics, which determines the values enshrined in folk knowledge, through which the structure of values in axiological linguistics was demonstrated. In conclusion, the recognition and evaluation of reality by ethnos (subject) in linguistics forms the ethno-cognitive evaluation system.